Secukinumab for Psoriasis in Obese Patients: Minireview and Clinical Experience - Rossana Tiberio; Francesca Graziola; Benedetta Miglino; Federica Veronese; Giordana Annali; Paola Savoia (Karger Publishers, 2019)
Psoriasis (PsO) has been associated with obesity, and its severity increases in obese subjects. The link between psoriatic condition and obesity is based on shared pathophysiological pathways where local and systemic inflammation promote each other; PsO is an inflammatory, immune-mediated disease, and the adipose tissue is the source of proinflammatory adipokines. Moreover, psoriatic arthritis (PsA) is an important comorbidity of PsO that reduces quality of life and makes difficult the patient's management. Treatment of obese subjects with moderate to severe PsO, even more if PsA is present, is challenging because of reduced efficacy of several systemic drugs and increased risk of adverse events. Secukinumab, a monoclonal antibody that selectively binds to and neutralizes interleukin 17A, shows efficacy on PsO in all body weight groups, even in the highest, whose response has a slight downward trend. Clinical features of two obese subjects, affected by PsO and PsA, successfully treated with secukinumab, are described.